Laparoscopic subtotal cholecystectomy for difficult cases of acute cholecystitis: a simple technique using barbed sutures - Sho Fujiwara; Kenji Kaino; Kazuki Iseya; Nozomi Koyamada (Surgical Case Reports)
Abstract Background Laparoscopic cholecystectomy (LC) for difficult acute cholecystitis (AC) cases bears a high risk of vasculobiliary injuries (VBI). The Tokyo Guidelines 2018 (TG18) recommend the use of bailout procedures and subtotal cholecystectomy to prevent VBI. Performing a safe LC is challenging, even when followed by an accurate pre-surgical assessment. Laparoscopic cholecystectomy (LSC) requires advanced skills, and there is a risk of recurrence of cancer and/or gallbladder stones (GBS) in the remnant gallbladder (GB). Moreover, it is sometimes impossible to safely close the cystic duct with either a loop tie or linear staples because of anatomical and fragility problems. Here, we report a novel technique employing barbed sutures for LSC in difficult AC cases. Case presentation We performed urgent LSC using barbed sutures for the stump of the cystic duct in two patients. In preoperative assessments, we found that these cases were qualified for operations rather than GB drainages, but the cystic ducts appeared difficult to close due to their severe inflammation and fragility during the operations. We applied barbed suture as a surrogate technique to close the stump of cystic duct. In patient 1, a 67-year-old woman with severe heart failure and type 2 diabetes mellitus was diagnosed with grade III AC. Pathological diagnosis was gangrenous cholecystitis. In patient 2, a 68-year-old woman who was referred to our hospital after 15 days of treatment for AC with antibiotics without drainage. The severity of AC was grade II according to TG18. Pathological diagnosis was acute-on-chronic cholecystitis. Both patients were discharged without complication. Conclusions The utilization of barbed sutures in LSC stems as a feasible and safe surrogate technique. Furthermore, this approach could decrease the risks associated with the remnant GB.